Evaluasi Model Exponential Generelized Autoregressive Conditional Heteroscedastic (EGARCH) - Novianti Dwi PujiAstuti; Suwanda (Bandung Conference Series: Statistics, 2022)
Abstract. In time series data that has a fairly high volatility, it is possible to have an error variance that is not constant (Heteroscedasticity). This is reflected in the square of error that also follows the time series model, for example the autoregressive (AR) model and the expectation of the conditional error square is not constant, the AR model of the square of error is called the Autoregressive Conditional Heteroscedastic (ARCH). The AR model that combines time series data and squared error is called Generalized Autoregressive Conditional Heteroscedastic (GARCH). However, the GARCH model ignores the asymmetric effect on the data. So Nelson (1991) developed the GARCH model to overcome the asymmetric problem with the Exponential GARCH model. The purpose of this study was to determine the symptoms of the EGARCH model and apply the EGARCH model in stock price index data at PT. Bank X in Indonesia. The data used is closing price data for the period January 2019 – December 2021. The results show that the Residual from GARCH(2.0) is used to test the effect of asymmetry. The best model used for forecasting based on the comparison results of MAPE, AIC and SIC values ​​from several other models is the EGARCH(2,1) model. Abstrak. Pada data deret waktu yang memiliki volatilitas cukup tinggi dimungkinkan memiliki varian error menjadi tidak konstan (Heteroskedastisitas). Hal ini tercermin dari kuadrat error yang juga mengikuti model deret waktu, misal model autoregressive (AR) dan ekpektasi kuadrat error bersyarat tidak konstan, model AR dari kuadrat error disebut Autoregressive Conditional Heteroscedastic (ARCH). Model AR yang menggabungkan data deret waktu dan kuadrat error disebut Generalized Autoregressive Conditional Heteroscedastic (GARCH). Namun model GARCH mengabaikan efek asimetris pada data. Sehingga Nelson (1991) mengembangkan model GARCH untuk mengatasi permasalahan asimetris dengan model Exponential GARCH. Tujuan dari penelitian ini adalah untuk mengetahui gejala model EGARCH dan menerapkan model EGARCH pada data indeks harga saham di PT. Bank X di Indonesia. Data yang digunakan merupakan data harga penutupan selama periode Januari 2019 – Desember 2021. Hasilnya menunjukkan bahwa Residual dari GARCH(2,0) dipakai untuk menguji pengaruh asimetri. Model terbaik yang digunakan untuk peramalan berdasarkan hasil perbandingan nilai MAPE, AIC maupun SIC dari beberapa model lainnya ialah model EGARCH(2,1).